Evaluation of Onchocerca volvulus-specific IgG4 subclass serology as an index of onchocerciasis transmission potential of three Gabonese villages. - Egwang, T G (1994)
The major objective of this study was to evaluate the usefulness of IgG4 ELISA and Western blot analysis, using a crude extract of Onchocerca volvulus adult worms as antigens, for diagnosing onchocerciasis in a Gabonese paediatric population with mixed filarial infections. The subjects had loaisis, streptocercosis or mansonellosis in addition to onchocerciasis. Control sera from loaisis or mansonellosis subjects residing outside the endemic zone were used to provide the cut-off point for positive results. The IgG4 ELISA had a specificity of 96% but a lower sensitivity of 78.7%. It detected 25 onchocerciasis cases out of 65 individuals who were negative on parasitological examination. Furthermore, the ELISA provided a more accurate picture of onchocerciasis transmission in a village with very low skin microfilarial load. A 27.5-kD antigen was identified on Western blots as a marker of onchocerciasis. The paediatric population provided a reliable window for assessing the parasitologic and serologic parameters in the three villages with disparate levels of onchocerciasis transmission.